Will Natural Media Make Online Physicians More Trustworthy? The Effect of Media Naturalness on Patients' Intention to Use HIT - Xiang, Shuting; Chen, Weiru; Wu, Banggang; Xiang, Dan; Wu, Shan (Frontiers in Psychology, 2022)
Although previous studies have recognized the important role of patients’ trust in promoting their intention to use health information technologies (HIT), most of those studies were under the “risk-benefit” theoretical framework. To deepen the understanding of patients’ online consultation decisions, this paper develops a dual-path model investigating how patients’ develop trust beliefs towards online physicians from the perspective of communication. Drawing on Medium Naturalness Theory, we propose that HIT medium naturalness will improve patients’ perception of communication efforts from online physicians, as well as decrease communication ambiguity between patients and online physicians. This will further strengthen patients’ trust towards online physicians and promote their intention to use HIT. Based on a two-wave survey from 361 participants, the empirical results demonstrated that the relationship between HIT medium naturalness and patients’ intention to use HIT is individually and serially mediated by two chains, including 1) perceived communication efforts and patients’ trust and 2) perceived communication ambiguity and patients’ trust. We thus contribute to related literature and also show practical implications.